2010
DOI: 10.20533/licej.2040.2589.2010.0007
|View full text |Cite
|
Sign up to set email alerts
|

Utilising Peer Coaching as a tool to improve student-teacher confidence and support the development of classroom practice

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 16 publications
0
18
0
Order By: Relevance
“…It is unclear whether developing confidence was a Zimbabwean phenomenon where the system undermined self-confidence/self-belief of professionally unqualified degreed teachers. Confidence is linked to performance because it increases motivation, perceptions, and thought processes (Prince et al, 2010). Often confident people are daring, open to learning, self-expressive, enjoy taking risks, and voice when they do not understand.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is unclear whether developing confidence was a Zimbabwean phenomenon where the system undermined self-confidence/self-belief of professionally unqualified degreed teachers. Confidence is linked to performance because it increases motivation, perceptions, and thought processes (Prince et al, 2010). Often confident people are daring, open to learning, self-expressive, enjoy taking risks, and voice when they do not understand.…”
Section: Discussionmentioning
confidence: 99%
“…Confidence is about being certain of one's abilities, related to self-esteem and optimism, belief in positive achievements and self-awareness involving ability to judge how well one can perform (Prince, Snowden, & Matthews, 2010). Two factors apparently contributed to developing confidence.…”
Section: Interviewmentioning
confidence: 99%
“…Confidence is understood as a multi-dimensional concept related to self-esteem, self-efficacy and optimism which manifests in one's belief in positive achievements, self-awareness and, ability to make judgments on how well or whether they can do something (Prince, Snowden & Matthews, 2010). Graven (2004) concluded that confidence has psychological/cognitive underpinnings which link it to internalized knowledge and beliefs.…”
Section: Growth In Students' Confidence Independence and Autonomymentioning
confidence: 99%
“…These characteristics are also vital for pre-service teachers as they effectively promote reflective practice and professional development. Prince et al (2010) contend that teacher confidence affects teacher-pupil interaction, the way teachers express themselves as individuals and how pupils respond to classroom instructions. Students also reported growth of independence and autonomy.…”
Section: Growth In Students' Confidence Independence and Autonomymentioning
confidence: 99%
“…Goker, 2006;Prince et al, 2010). The issue of peer coaching for professional develoment of teachers has inspired a number of studies both in the field of pre-service teacher education and in-service teacher development.…”
Section: Introductionmentioning
confidence: 99%